Morphogenetic expression of Bacteroides nodosus fimbriae in Pseudomonas aeruginosa. - Mattick, J S (1987)
Type 4 fimbriae are found in a range of pathogenic bacteria, including Bacteroides nodosus, Moraxella bovis, Neisseria gonorrhoeae, and Pseudomonas aeruginosa. The structural subunits of these fimbriae all contain a highly conserved hydrophobic amino-terminal sequence preceding a variable hydrophilic carboxy-terminal region. We show here that recombinant P. aeruginosa cells containing the B. nodosus fimbrial subunit gene under the control of a strong promoter (pL, from bacteriophage lambda) produced large amounts of fimbriae that were structurally and antigenically indistinguishable from those produced by B. nodosus. This was demonstrated by fimbrial isolation and purification, electrophoretic and Western transfer analyses, and immunogold labeling and electron microscopy. These results suggest that type 4 fimbriated bacteria use a common mechanism for fimbrial assembly and that the structural subunits are interchangeable, thereby providing a basis for the development of multivalent vaccines.